PEMANFAATAN E-LEARNING SEBAGAI ALTERNATIF PENGGANTI PELATIHAN TATAP MUKA BAGI PENDIDIK DAN TENAGA KEPENDIDIKAN PENDIDIKAN NONFORMAL - Putu Ashintya Widhiartha (JIV-Jurnal Ilmiah Visi, 2009)
Recently, there have been massive efforts in E-learning implementation for educator training around the world. E-learning could shortly be defined as a web-based educational system on platform with Internet,  Intranet or computer access. This article describes the possibility to implement E-learning for non-formal teacher training in Indonesia. Non-formal teachers have to realize that they face new challenge to improve their competencies and must be able to make appropriate use of Information and Communication Technologies (ICT). This is a challenge that has caused non-formal teachers to reflect on how they adapt to new educational changes without compromising the quality of education. In addition E-learning also could be used to reduce the enormous cost of conventional non-formal teacher training.